2016
DOI: 10.1163/22134468-00002075
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expectation Indexed by Pupillary Response

Abstract: Forming temporal expectations plays an instrumental role for the optimization of behavior and allocation of attentional resources. Although the effects of temporal expectations on visual attention are well-established, the question of whether temporal predictions modulate the behavioral outputs of the autonomic nervous system such as the pupillary response remains unanswered. Therefore, this study aimed to obtain an online measure of pupil size while human participants were asked to differentiate between visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 1 publication
0
21
2
Order By: Relevance
“…While we did not record EEG in Experiment 2, we explored the use of pupillary responses at interval offset as a potential measure to dissociate sensory magnitude effects from arousal. In particular, we assessed whether marker changes affected pupil sizes, either by causing larger pupil dilation, a signature of arousal or surprise (Akdoğan et al, 2016; Braem et al, 2015; Satterthwaite et al, 2007), or by evoking stronger constriction responses which are associated with stronger pre-attentive sensory processing (Binda et al, 2013; Mathôt et al, 2014; Naber et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not record EEG in Experiment 2, we explored the use of pupillary responses at interval offset as a potential measure to dissociate sensory magnitude effects from arousal. In particular, we assessed whether marker changes affected pupil sizes, either by causing larger pupil dilation, a signature of arousal or surprise (Akdoğan et al, 2016; Braem et al, 2015; Satterthwaite et al, 2007), or by evoking stronger constriction responses which are associated with stronger pre-attentive sensory processing (Binda et al, 2013; Mathôt et al, 2014; Naber et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Accompanying the behavioral results, we analyzed pupil size as another proxy for sensory magnitude and arousal. That is, previous work has shown that bottom-up stimulus strength can affect the pupil constriction response (Binda, Pereverzeva, & Murray, 2013; Mathôt, Dalmaijer, Grainger, & Stigchel, 2014; Naber, Frässle, Rutishauser, & Einhäuser, 2013), whereas dilation is often used as a signature of arousal or surprise (Akdoğan, Balcı, & Rijn, 2016; Braem, Coenen, Bombeke, van Bochove, & Notebaert, 2015; Satterthwaite et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This casts doubts on the exact mechanisms that are reflected in the prestimulus pupil size. With regard to temporal preparation, several studies have found increased pupil diameter prior to target onset in fixed foreperiod tasks with predictable target timing (Akdoǧan & van Rijn, 2016;Unsworth et al, 2018;Van der Molen, Boomsma, Jennings, & Nieuwboer, 1989). In contrast, prestimulus pupil increase in variable foreperiod paradigms is either smaller compared to fixed foreperiod tasks (Jennings, Molen, & Steinhauer, 1998) or unreported (Unsworth et al, 2018).…”
Section: Pupil-performance Associationsmentioning
confidence: 99%
“…In particular, prestimulus pupil diameter in anticipation of a target has been associated with proactive, preparatory attention, whereas phasic poststimulus pupil responses may reflect reactive attention (Chatham, Frank, & Munakata, ; Chiew & Braver, ). Prestimulus pupil diameter is found to increase prior to stimulus onset in predictable timing paradigms (Akdoǧan & van Rijn, ; Unsworth, Robison, & Miller, ), reflecting attentional readiness. Moreover, reward manipulations have been shown to increase prestimulus pupil size (Chiew & Braver, ), possibly reflecting increased proactive attention.…”
Section: Introductionmentioning
confidence: 99%
“…1. Exclusion of outlier samples (Akdoğan, Balcı, & van Rijn, 2016;Cohen et al, 2015;Wainstein et al, 2017). CHAP converts pupil size data to z score values based on the mean and standard deviation (SD) calculated for each trial separately.…”
Section: Data Preprocessingmentioning
confidence: 99%